Novice Counselor's Work Readiness - Tri Sutanti; Suharsimi Arikunto; Irvan Budhi Handaka (Universitas Ahmad Dahlan, 2021)
This descriptive study aims to find out the novice counselors’ work readiness. To this end, fifty-four novice counselors graduated from the guidance and counseling department of Ahmad Dahlan University were recruited. The data were collected using a work readiness scale and analyzed using a quantitative descriptive technique. The result showed that the school counselors’ strongest aspect lay in work attitude, while the weakest aspect lay in interpersonal communication. Based on the focus group discussion, novice counselors still faced some difficulties when providing guidance and counseling services at school. The most frequently found obstacles were their ability to deal with the students’ mental, assertiveness, group counseling services, collaboration service, and service management. This study can be used as the basis to develop a service or training strategy to improve the novice counselors’ work readiness.